Applications of methods of psychological support developed for astronauts for use in medical settings - Rozanov, Ivan A.; Ryumin, Oleg; Karpova, Olga; Shved, Dmitry; Savinkina, Alexandra; Kuznetsova, Polina; Diaz Rey, Nicole; Shishenina, Ksenia; Gushin, Vadim (Frontiers in Physiology, 2022)
During recent 40 years psychological support (PS) of cosmonauts and astronauts remained an important part of the regular biomedical provision of space crews during extended orbital flights. It includes well-developed principals and a set of methods that proved their effectiveness for the maintenance of behavioral health under extreme conditions of space flight. The main principal of the inflight PS is restoration of the usual sensory input to compensate monotony and lack of external stimuli as a result of long stay under isolation and confinement. Risk factors to the psychological health and well-being, defined for the astronauts, such as sensory and social deprivation, monotony, confinement, lack of privacy also remain part and parcel of several civil professions. They include polar wintering, submarines, working at oil platforms, ocean fishing, mountain climbing, professional sport, etc. Most of these factors also adversely affect the healing rate of a large contingent of medical hospitals, especially bedridden patients with chronic illnesses. Finally, due to the negative epidemiological situation associated with the spread of COVID-19, an increasingly wide range of citizens who are forced to stay under self-isolation are facing with negative manifestations of the deprivation phenomena described above. Several cases of successful utilization of PS under isolation, monotony, crowding and confinement are presented. Thus, we assume that the use of psychological support methods developed for space flights could be extremely relevant in civil medicine and everyday life.